2003
DOI: 10.1159/000074222
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the Immunosuppressive Treatment of Patients with Severe Acquired Aplastic Anemia: A Single Institution Study

Abstract: In México, only few patients can afford adequate treatment for aplastic anemia. In a single institution 61 individuals with severe aplastic anemia (SAA) were identified; of these, 33 were followed for at least 3 months, 26 could be treated with immunosuppression (IS), 20 with antithymocyte globulin and cyclosporin A (ATG + CyA) and 6 with CyA, whereas 7 individuals were given only anabolic androgens. In the patients treated with IS a complete remission was achieved in 12 and a partial remission in 6, the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Barring specific contraindications, patients with SAA should proceed straight to HSCT if they have HLA-identical sibling donors [18]. However, Our study demonstrated overall survival equivalent to that previously reported for HLA-identical BMT recipients [19,20], which is superior to that reported for those treated with IST alone [21,22]. An increased risk of evolution to myelodysplastic syndrome/acute myeloblastic leukemia has been observed in long-term survivors of aplastic anemia not treated with HSCT [23].…”
Section: Discussionsupporting
confidence: 56%
“…Barring specific contraindications, patients with SAA should proceed straight to HSCT if they have HLA-identical sibling donors [18]. However, Our study demonstrated overall survival equivalent to that previously reported for HLA-identical BMT recipients [19,20], which is superior to that reported for those treated with IST alone [21,22]. An increased risk of evolution to myelodysplastic syndrome/acute myeloblastic leukemia has been observed in long-term survivors of aplastic anemia not treated with HSCT [23].…”
Section: Discussionsupporting
confidence: 56%
“…Patients met the criteria for the diagnosis of severe AA [1,6]. All patients had failed to respond to conventional treatment with immunosuppression using ATG and/or cyclosporin and had been heavily transfused (see Table I).…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…Mexico is a country with a large number of cases of AA [6]; however, due to financial and idiosyncratic factors, the elapsed time from diagnosis to hematopoietic cell transplantation is usually long, leading to AA patients being multiply transfused and highly sensitized to HLA antigens before transplant is undertaken. We have studied the effectiveness of peripheral blood stem cells and a fludarabine/cyclophosphamide-based conditioning regimen without ATG or lymph node irradiation in 23 AA patients who had no response to previous conventional pharmacologic treatment, including androgens and immunosuppressive therapy, and who had been heavily transfused.…”
Section: Introductionmentioning
confidence: 99%
“…For determining the incidence of LPD after IST, we searched Medline (Pubmed) for published articles about the long-term results of IST for AA [1, 4, 5,7,8,9,10,11,12,13,14,15,16,17,18]. We found 3 cases with LPD among the published studies [5, 7, 12].…”
Section: Discussionmentioning
confidence: 99%